Midterm Radiographic and Functional Outcomes of the Anterior Subcutaneous Internal Pelvic Fixator (INFIX) for Pelvic Ring Injuries. Issue 5 (May 2017) - Vaidya, Rahul; Martin, Adam Jonathan; Roth, Matthew; Tonnos, Frederick; Oliphant, Bryant; Carlson, Jon
Abstract : Objective: To describe our experience using the anterior internal pelvic fixator (INFIX) for treating pelvic ring injuries. Design: Case Series. Setting: Level 1 Trauma Center. Patients: Eighty-three patients with pelvic ring injuries were treated with INFIX. Follow-up average was 35 months (range 12–80.33). Intervention: Surgical treatment of pelvic ring injuries included reduction, appropriate posterior fixation, and INFIX placement. Outcome Measurements: Reduction using the pelvic deformity index and pubic symphysis widening, Majeed functional scores, complications; infection, implant failure, heterotopic ossification (HO), nerve injury, and pain. Results: All patients healed in an appropriate time frame (full weight bearing 12 weeks postoperation). The average pelvic deformity index reduction (injury = 0.0420 ± 0.0412, latest FU = 0.0254 ± 0.0243) was 39.58%. The average reduction of pubic symphysis injuries was 56.92%. The average Majeed score of patients at latest follow-up was 78.77 (range 47–100). Complications were 3 infections, 1 case of implant failure, 2 cases implantation too deep, 7 cases of lateral femoral cutaneous nerve irritation, and 3 cases of pain associated with the device. HO was seen in >50% of the patients, correlated with increased age ( P < 0.007), injury severity score ( P < 0.05) but only 1 case was symptomatic. Conclusions: The pelvic injuries had good functional and radiological outcomes with INFIX and the appropriate posterior fixation. The downside is removal requiring a second anesthetic, there is a learning curve, HO often occurs, the lateral femoral cutaneous nerve may get irritated which often resolves once the implants are removed. Surgery-specific implants need to be developed. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.